Studies of OFDM signal for broadband optical access networks - Chow, C W; Yeh, C H; Wang, C H; Wu, C L; Chi, S; Chinlon Lin (IEEE journal on selected areas in communications, 2010)
Using orthogonal-frequency-division-multiplexing (OFDM) format for passive optical network (PON) is a subject of great interest for recent research works. OFDM signal has high spectral efficiency, high tolerance to the fiber chromatic dispersion and the high flexibility on both multiple services provisioning and dynamic bandwidth allocation. In this paper we study the use of OFDM signals for optical access networks, including carrier distributed PON, heterogeneous optical wired/wireless network and a 100 Gb/s OFDM-PON. We first quantify the performance of the OFDM signal when subjected to the noise produced by two different Rayleigh backscattering (RB) components that are present in the carrier-distributed PON. Then, based on these results, we also study the possibility of using OFDM for signal remodulation in a long-reach (LR)-PON. We propose carrier-distributed OFDM PONs using a dual-feeder fiber architecture and wavelength-shifting to mitigate the RB noise. Afterwards, we propose heterogeneous optical wired/wireless access networks, combining 10 Gb/s PON and 10 Gb/s OFDM radio-over-fiber (ROF) network. Finally, we propose a 100 Gb/s OFDM-PON using subcarrier multiplexing (SCM).